The influence of the EUV spectrum on plasma induced by EUV radiation in argon and hydrogen gas. (16th December 2015) - van der Horst, R M; Osorio, E A; Banine, V Y; Beckers, J
Abstract: Plasmas induced by EUV radiation are scarcely investigated, although they are unique since they are created without any discharge. These plasmas are also of interest from an applicational point of view, since they are related to the lifetime of optics in EUV lithography tools. In order to assess this impact, it is essential to characterize and understand EUV-induced plasma. In this contribution the influence of the background gas (argon and hydrogen) in the lithography tool and the spectrum of the illumination source on the electron density of EUV-induced plasma is investigated using microwave cavity resonance spectroscopy. The experimental results showed that out-of-band radiation (>20 nm) is the main contributor to EUV-induced plasma in both argon and hydrogen. In hydrogen, this contribution is relatively more important than in argon due to the stronger wavelength dependence of the photoionization cross section of hydrogen than of argon. Furthermore, the production of electrons by out-of-band radiation lasts longer than the production by in-band radiation (10–20 nm) due to the longer temporal width of out-of-band radiation. Finally, the obtained results correspond reasonably well with estimates from a simplified absorption model.